Relative Contributions of Osteogenic Tissues to New Bone Formation in Periosteal Distraction Osteogenesis: Histological and Histomorphometrical Evaluation in a Rat Calvaria. (16th November 2011) - Saulacic, Nikola; Hug, Cladius; Bosshardt, Dieter D.; Schaller, Benoit; Buser, Daniel; Haeniwa, Hideya; Iizuka, Tateyuki
ABSTRACT Background: The relative contributions of different, potential factors to new bone formation in periosteal distraction osteogenesis are unknown. Purpose: The aim of the present study was to assess the influence of original bone and periosteum on bone formation during periosteal distraction osteogenesis in a rat calvarial model by means of histology and histomorphometry. Methods: A total of 48 rats were used for the experiment. The contribution of the periosteum was assessed by either intact or incised periosteum or an occlusive versus a perforated distraction plate. The cortical bone was either left intact or perforated. Animals were divided in eight experimental groups considering the three possible treatment modalities. All animals were subjected to a 7‐day latency period, a 10‐day distraction period and a 7‐day consolidation period. The newly formed bone was analyzed histologically and histomorphometrically. Results: New, mainly woven bone was found in all groups. Differences in the maximum height of new bone were observed and depended on location. Under the distraction plate, statistically significant differences in maximum bone height were found between the group with perforations in both cortical bone and distraction plate and the group without such perforations. Conclusions: If the marrow cavities were not opened, the contribution to new bone formation was dominant from the periosteum. If the bone perforations opened the marrow cavities, a significant contribution to new bone formation originated from the native bone.